2013
DOI: 10.1089/vbz.2012.1055
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Susceptibility Status ofAnophelesMosquitoes in Four Flood-Affected Districts of South Punjab, Pakistan

Abstract: Recent floods drastically increased the burden of disease, in particular the incidence of malaria, in the southern districts of the Punjab province in Pakistan. Control of malaria vector mosquitoes in these districts requires the adoption of an appropriate evidence-based policy on the use of pesticides, and having the latest information on the insecticide resistance status of malaria vector mosquitoes is essential for designing effective disease prevention policy. Using World Health Organization (WHO) test kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…against DDT, deltamethrin and permethrin. (Rathor et al ., ), which is also an accordance with the observations of the present study. Another study conducted in district MirPur Khas, Pakistan, aimied to evaluate the susceptibility of An.…”
Section: Discussionsupporting
confidence: 94%
“…against DDT, deltamethrin and permethrin. (Rathor et al ., ), which is also an accordance with the observations of the present study. Another study conducted in district MirPur Khas, Pakistan, aimied to evaluate the susceptibility of An.…”
Section: Discussionsupporting
confidence: 94%
“…aegypti 5,21,22 , Culex quinquefasciatus Say 23 , Anopheles spp. 24,25 , and Periplaneta americana L. 26 . Previously, we have reported resistance development in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Anopheles stephensi from Lahore, Pakistan was resistant to DDT and malathion [80]. The species proved to be resistant to DDT, malathion, deltamethrin and lambda-cyhalothrin in South Punjab [81]. In another study in Punjab Province, the species was found to be significantly resistant to DDT, dieldrin and malathion while being susceptible to permethrin, deltamethrin and fenitrothion [29].…”
Section: Insecticide Resistance In Anopheles Stephensi In Other Who/ mentioning
confidence: 99%